A Methodology for Decision Support for Implementation of Cloud Computing IT Services - Adela Tušanová (Kvalita Inovácia Prosperita, 2014)
The paper deals with the decision of small and medium-sized software companies in transition to SaaS model. The goal of the research is to design a comprehensive methodic to support decision making based on actual data of the company itself. Based on a careful analysis, taxonomy of costs, revenue streams and decision-making criteria are proposed in the paper. On the basis of multi-criteria decision-making methods, each alternative is evaluated and the alternative with the highest score is identified as the most appropriate. The proposed methodic is implemented as a web application and verified through  case studies.